2015
DOI: 10.1007/s10098-015-0915-z
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on pursuit of sustainability: challenges for engineering community

Abstract: Sustainability is a keyword commonly used by researchers and practitioners globally. However, even defining the goals of sustainability is fraught with difficulties and hence attaining it is nearly impossible. Since sustainability is a property of the entire system, engineering sustainability requires the boundaries of the system greatly expanded. The thinking of sustainability also brings in larger time scales. In this article, I present a perspective on journey toward sustainability using systems analysis ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The dynamics and complexity of the SDGs should be considered when prioritizing and optimizing the goals [10]. It is clear that there is an urgent need for a holistic and systematic perspective when seeking a feasible solution to harmonizing the SDGs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics and complexity of the SDGs should be considered when prioritizing and optimizing the goals [10]. It is clear that there is an urgent need for a holistic and systematic perspective when seeking a feasible solution to harmonizing the SDGs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These concepts are derived from the financial and economics literature and engineering optimal control theory. These concepts could be extended to studying sustainability as presented in the recent literature ( Shastri and Diwekar, 2008 ; Shastri et al., 2008a , Shastri et al., 2008b ; Diwekar and Shastri, 2010 ; Diwekar, 2012b , Diwekar, 2015 ; Doshi et al., 2015 , Rodriguez-Gonzalez et al., 2019 ).…”
Section: Global Sustainability and Stochastic Processesmentioning
confidence: 99%
“…Other researchers have investigated the funding, financing and policy incentives for sustainable, higher-performing buildings. For example, Diwekar (2015) suggests a more holistic perspective is required for engineering sustainability. Chen and Hong (2015) indicate that, from a Chinese perspective, subsidies do play a role in incentivising green buildings, and that improving information flow will contribute to more green building, while Staniškis and Stasiškienë (2003) presented a model for facilitating cleaner production incentives in developing countries.…”
Section: Limitations and Further Workmentioning
confidence: 99%
“…Research by Webb, Aye and Green (2013, 2015, 2018; Webb, Hertzsch and Green (2011) has shown that specific biomimetic strategies could improve the thermal performance of building envelopes. Testing of the efficacy of the biomimetic design was accomplished through digital modelling and building energy simulation.…”
Section: Introductionmentioning
confidence: 99%